Determinação da área de folhas do café (Coffea arabica L.cv. "Bourbon Amarelo') - Santos Barros, Raimundo; Maestri, Moacyr; Vieira, Manoel; Julião Braga Filho, Luís (Revista Ceres, 2025)
To estimate the area of coffee (Coffea arabica L.cv. 'Bourbon Amarelo") leaves, the linear regressions Y = 0,262+0.664 X and Y = 0,67 X, where the variable is the rectangle circunscribe to the leaf (X = CL), were found to be statistically much better than the two logarithmic equations, either as a function of lenght (C) or mximum width (L), log Y = -0,619 + 2,091 log C and log Y = 0,223 + 1,927 log L. The two linear equations are statistically equivalent. but he equation giving a line through the origin is easier to handle. The logarithmic equations should not be used, as they are less precise.